Vascular inflammation, atherosclerosis, and lipid metabolism and the occurrence of non-high albuminuria diabetic kidney disease: A cross-sectional study. (February 2021) - Yang, Yuwei; Xu, Peng; Liu, Yan; Chen, Xiaohong; He, Yiyang; Feng, Jiafu
Aim: Atherosclerosis involves vascular endothelial damage and lipid metabolism disorder, which is closely related to the occurrence and development of diabetic kidney disease (DKD). However, studies on non-high albuminuria DKD (NHADKD) with an albumin to creatinine ratio (ACR) <30 mg/g are rare. This study is to investigate the relationship between atherogenic factors and the occurrence of NHADKD. Methods: Serum lipid indicators, lipoprotein-associated phospholipase A2 (Lip-PLA2) and homocysteine levels were measured in 1116 subjects to analyze their relationship with NHADKD. Results: Among all subjects, Lip-PLA2 had the closest but relatively weak correlation with ACR ( r = 0.297, p < 0.001) and only homocysteine was moderately correlated with eGFR ( r = −0.465, p < 0.001). However, in patients with NHADKD, these atherosclerotic factors were weakly correlated or uncorrelated with eGFR (max. | r | = 0.247). Stratified risk analysis showed that when ACR was <10 mg/g, homocysteine [OR = 6.97(4.07–11.95)], total cholesterol (total-Chol) [OR = 6.04(3.03–12.04)], and high-density lipoprotein cholesterol (HDL-Chol) [OR = 5.09(2.99–8.64)] were risk factors for NHADKD. There was no significant difference of OR between these three factors ( Z = 0.430–1.044, all p > 0.05). When ACR was ⩾10mg/g, homocysteine [OR = 17.26(9.67–30.82)] and total-Chol [OR = 5.63(2.95–10.76)] were risk factors for NHADKD, and ORhomocysteine was significantly higher than ORtotal-Chol ( Z = 3.023, p < 0.05). Conclusions: The occurrence of NHADKD may be related to the levels of homocysteine, total-Chol, HDL-Chol, and Lip-PLA2 in blood. Among them, homocysteine may be most closely related to NHADKD.